Status of Serum Lipids in Individuals with Depression - Sharma, Saroj; Shrestha, Lilee; Ojha, Saroj Prasad; Jha, Bharat (Annals of Clinical Chemistry and Laboratory Medicine, 2016)
BACKGROUND Epidemiological studies have shown the association between depressive illness with cardiovascular disease (CVD). Serum lipid abnormality is one of the major risk factor for cardiovascular disease. Therefore, this study aimed to access the status of Serum lipid in individuals with depression. METHODS A cross sectional study was carried out in Tribhuvan University Teaching Hospital (TUTH) over the period of 16 month from June 2011 to October 2012. A total of 85 individuals with depression and the same number of age-sex matched controls were enrolled in the study. Depression was diagnosed by Consultant Psychiatrist as per ICD-10-DCR criteria. Serum Lipid profile was assessed from both test and control groups after an overnight fasting. A written consent was taken for anthropometric data and sample collection. RESULTS Large numbers of depressive individuals were found to have Dyslipidemia. Total Cholesterol, TG was found to be significantly higher in test group compared to control. The mean HDL-cholesterol was found significantly lower in test group compared to control. No significant differences between test and control were observed in VLDL-cholesterol and LDL-cholesterol. CONCLUSIONS Serum lipid profile abnormalities are found high in individuals with depression. Based on the observation of this study, Serum Lipid abnormalities seen in individuals with Depression make them vulnerable to cardiovascular disease.